Peran Pengalaman Kerja Dalam Meningkatkan Kinerja Karyawan (Studi Kasus Dinas Perkebunan Provinsi Sumatra Utara) - Imron Berutu; Muhammad Ikhsan Harahap (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Improving the performance of our company employees requires work experience. Employee work experience shows skill proficiency. Employees who have worked for several years have different types of work experience to solve different types of problems within the company. Quality Resources to Improve Work Performance The purpose of this study is to improve employee performance in order to achieve a high level of performance based on the results of the existing literature review, namely to explain scientifically the role of work experience. Work done on a complete job. Improve employee performance.